Transfiguration of the Sandwich Generation Concept in Islam - Salamuddin, Ahmad; Fahrudin, F; Rahmat, Munawar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The concept of sandwich generation that is developing today always has a negative connotation, especially if it is included in the Islamic context, it will not find its equivalent, it even tends to be incompatible with the Islamic point of view which states that sandwich generation gives a heavy burden in taking care of 3 generations at once, namely his parents, himself and his younger brother, many of which cause him mental health and excessive depression because of understanding the concept of sandwich generation like most. Therefore, this research aims to provide a configuration of the concept so that it can be accepted and understood properly in the Islamic point of view. In this research, the author uses qualitative research with a literature study approach or Book Review and also a Qur'anic approach. The result of this research is that the configuration of the concept carried out in the sandwich generation has 3 main points of discussion, namely regarding morals to both parents, to siblings or others, and also belief in sustenance, as well as taking an approach through Al-Qur'an verses and straightening out concepts that can be accepted with a positive connotation in understanding the sandwich generation.